Dynamic Margins of Stability During Robot-Assisted Walking in Able-Bodied Individuals: A Preliminary Study - Ramanujam, Arvind; Momeni, Kamyar; Ravi, Manikandan; Augustine, Jonathan; Garbarini, Erica; Barrance, Peter; Spungen, Ann M.; Asselin, Pierre; Knezevic, Steven; Forrest, Gail F. (Frontiers in Robotics and AI, 2020)
Background: Gait analysis studies during robot-assisted walking have been predominantly focused on lower limb biomechanics. During robot-assisted walking, the users’ interaction with the robot and their adaptations translate into altered gait mechanics. Hence, robust and objective metrics for quantifying walking performance during robot-assisted gait are especially relevant as it relates to dynamic stability. In this study, we assessed bi-planar dynamic stability margins for healthy adults during robot-assisted walking using EksoGTTM, ReWalkTM, and Indego® compared to independent overground walking at slow, self-selected, and fast speeds. Further, we examined the use of forearm crutches and its influence on dynamic gait stability margins. Methods: Kinematic data were collected at 60Hz under several walking conditions with and without the robotic exoskeleton for six healthy controls. Outcome measures included (i) Whole-body center of mass (CoM), and extrapolated CoM (XCoM), (ii) Base of Support (BoS), (iii) Margin of Stability (MoS) with respect to both feet and bilateral crutches. Results: Stability outcomes during exoskeleton-assisted walking at self-selected, comfortable walking speeds were significantly (p<0.05) different compared to overground walking at self-selected speeds. Unlike overground walking, the control mechanisms for stability using these exoskeletons were not related to walking speed. MoS were lower during the single support phase of gait, especially in the medial-lateral direction for all devices. MoS relative to feet were significantly (p<0.05) lower than those relative to crutches. The spatial location of crutches during exoskeleton-assisted walking pushed the whole-body center of mass, during single support, beyond the lateral boundary of the lead foot increasing the risk for falls if crutch slippage were to occur. Conclusion: Careful consideration of crutch placement is critical to ensuring the margins of stability are always within the limits of the base of support to control stability and decrease fall risk.